PENGARUH KANDANG NAUNGAN DAN TANPA NAUNGAN TERHADAP FREKUENSI PERNAFASAN DAN SUHU TUBUH KAMBING KACANG JANTAN DI LAHAN KERING KEPULAUAN - Bachtaruddin Badewi; Bambang Hadisutanto; Merianse Djita; Molbeka Marthina Manikari; Maria Indriana Sasi; Rivandi Ora (Politeknik Pertanian Negeri Kupang, 2018)
The temperature of the environment outside the body increases, especially cattle, goats that are kept in cages without shade will cause manifestations of these reactions, namely increased frequency of respiration and body temperature and behavior that shows heat. The purpose of this study was to compare changes in respiratory frequency and body temperature of goat nuts, which were shaded with shade and without shade on the island's dry land. This study used fourteen 14 years old male goats. those goats are placed in 7 roofed cages and 7 cages without roof. The study was conducted for 30 days. The variables observed were respiratory frequency and body temperature. The analysis of the results of the study was carried out by t-student test by comparing the goat's breeds in cages with shade and cages without shade. The results of the t-test analysis show that the effect of roofed cages and without roof does not give a difference in respiratory frequency and body temperature. Goats raised in Kupang have implemented for a long time, both in the atmosphere of the cage withroof and without, so that goats have experienced acclimatization, which is a long-term physiological adjustment that causes increased tolerance to stressful complex and continuous climate which usually occurs in the field. This is the basis that the respiratory frequency and body temperature ofthe goats kept in a roofed stall and without, do not have a significant effect. It can be concluded that shade cages and without shade do not affect respiratory frequency and body temperature.